If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 3) + -1x(4 + -1x) = x(x + 1) + 3(x + 4) Reorder the terms: 4(3 + 2x) + -1x(4 + -1x) = x(x + 1) + 3(x + 4) (3 * 4 + 2x * 4) + -1x(4 + -1x) = x(x + 1) + 3(x + 4) (12 + 8x) + -1x(4 + -1x) = x(x + 1) + 3(x + 4) 12 + 8x + (4 * -1x + -1x * -1x) = x(x + 1) + 3(x + 4) 12 + 8x + (-4x + 1x2) = x(x + 1) + 3(x + 4) Combine like terms: 8x + -4x = 4x 12 + 4x + 1x2 = x(x + 1) + 3(x + 4) Reorder the terms: 12 + 4x + 1x2 = x(1 + x) + 3(x + 4) 12 + 4x + 1x2 = (1 * x + x * x) + 3(x + 4) 12 + 4x + 1x2 = (1x + x2) + 3(x + 4) Reorder the terms: 12 + 4x + 1x2 = 1x + x2 + 3(4 + x) 12 + 4x + 1x2 = 1x + x2 + (4 * 3 + x * 3) 12 + 4x + 1x2 = 1x + x2 + (12 + 3x) Reorder the terms: 12 + 4x + 1x2 = 12 + 1x + 3x + x2 Combine like terms: 1x + 3x = 4x 12 + 4x + 1x2 = 12 + 4x + x2 Add '-12' to each side of the equation. 12 + 4x + -12 + 1x2 = 12 + 4x + -12 + x2 Reorder the terms: 12 + -12 + 4x + 1x2 = 12 + 4x + -12 + x2 Combine like terms: 12 + -12 = 0 0 + 4x + 1x2 = 12 + 4x + -12 + x2 4x + 1x2 = 12 + 4x + -12 + x2 Reorder the terms: 4x + 1x2 = 12 + -12 + 4x + x2 Combine like terms: 12 + -12 = 0 4x + 1x2 = 0 + 4x + x2 4x + 1x2 = 4x + x2 Add '-4x' to each side of the equation. 4x + -4x + 1x2 = 4x + -4x + x2 Combine like terms: 4x + -4x = 0 0 + 1x2 = 4x + -4x + x2 1x2 = 4x + -4x + x2 Combine like terms: 4x + -4x = 0 1x2 = 0 + x2 1x2 = x2 Solving 1x2 = x2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x2' to each side of the equation. 1x2 + -1x2 = x2 + -1x2 Combine like terms: 1x2 + -1x2 = 0 0 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| 4xsquared-13x+9=-5x+6 | | 9-3k=0 | | 8t-14=0 | | 8m+3n-3m+10n= | | 48x^2-1537x-3076= | | 9x^2-2x^3=0 | | 3f^2+2f-f^2+4f= | | x^3+3x^2-8x+4=0 | | (x+9)2=81 | | 5+y=2y-4 | | 5x^2-30x+9-20x^2-25x+20x^2+5x-5x^2= | | 3x+15=11-x | | 5x*(x-1)= | | 5x*(4x-5)= | | 3x+5=11-x | | Log(11-x)-log(2-x)=1 | | X^4-8x^3+18x^2-8x-1=0 | | 2xsquared-16=0 | | 9(x-6)=4x | | 25=(3x-2)(2x+5)(3x-2)2 | | 25=(3x-2)(2x+5)(3x-2) | | 8x-7w+5x+8y+5y+3w= | | 5x-3=x+7+3 | | 137+x=428 | | X^3+4x^3+4x=0 | | 5y-8=22-y | | 10x+5y+7z-5x+3z-9y= | | 11a-16=6a-1 | | 4y-14=18whatisy | | 8t+2=3t+12 | | 6.5=2x+3 | | 5+2x=5x-3(x-1)+2 |